PEMANFAATAN DIGITAL MARKETING SEBAGAI STRATEGI PEMASARAN PADA UMKM ISTANA RENDANG - Rafnel Azhari; Faidil Tanjung; Yulianti Fitri Kurnia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Istana Rendang, as the Micro, Small and Medium Enterprises (MSMEs), is one of the Rendang businesses located in Nagari Mungka, Regency of Lima Puluh Kota. This business of curry cooked beef has been running since 2003. The problems faced by MSMEs are the problem of marketing conventional products and the absence of a Home Industry Food certificate (P-IRT). The purpose of this community service activity is to help improve the marketing capabilities of Rendang products through the application of a digital marketing system. The implications of the system must be complemented by product quality improvement, which includes compliance with legality and improvement of product packaging. This activity was carried out through 3 stages, namely (1) socialization and assistance in obtaining product P-IRT certificates, (2) modification of product packaging and digital marketing training, and (3) monitoring and evaluation of activities. Through this service activity, P-IRT certificates were obtained for products of Rendang of dried meat, Rendang of dried cow's lung, Rendang of egg, and Rendang of vegetables. Furthermore, there were improvements to Rendang packaging and added digital marketing channels through the Instagram and Shopee applications. Mentoring activities need to be developed to help the Istana Rendang grow by maximizing online marketing.